Fisheries College, University of Agricultural Sciences, Mangalore-1 - Gupta, T R Chandrasekhara (Indian Journal of Fisheries, 2011)
An instance of intestinal abnormality in the ribbon fish, Trichiurus lepturus Linnaeus is described. The intestine was unusually short, opening at a much anteriorly shifted anal aperture which, in the normal condition, remains close to the urinogenital aperture.